2010
DOI: 10.1007/s11912-010-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90: A Drug Target?

Abstract: Heat shock protein 90 (Hsp90) is a molecular chaperone involved in the trafficking of proteins in the cell. Under stressful conditions, Hsp90 stabilizes its client proteins and provides protection to the cell against cellular stressors such as in cancer cells. Disruption of Hsp90 leads to client protein degradation and often cell death. As Hsp90 has been found to be either overexpressed or constitutively more active in cancer cells, inhibitors of Hsp90 may have cancer cell selectivity. The N-terminal inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 28 publications
0
70
0
Order By: Relevance
“…Furthermore, Hsp90 is constitutively, and 2-10 times more expressed in tumor cells than in normal ones, which means, that the correct function of Hsp90 is essential for the growth and survival of tumor cells (11). Hsp90 inhibition may lead to the degradation of proteins involved in the so-called six main characteristics of cancer: i) the ability to produce growth factors, ii) resistance to anticancer agents, iii) avoidance of apoptosis, iv) unlimited replicative potential, v) uninterrupted angiogenesis and vi) invasiveness and metastasis (8,12,13). The Hsp90 monomer is composed of four domains: a highly conserved N-and C-terminal domain, a middle domain and a charged linker region that connects to both N-terminal as well as middle domain (14).…”
Section: Hsp90 Inhibitor As a Sensitizer Of Cancer Cells To Differentmentioning
confidence: 99%
“…Furthermore, Hsp90 is constitutively, and 2-10 times more expressed in tumor cells than in normal ones, which means, that the correct function of Hsp90 is essential for the growth and survival of tumor cells (11). Hsp90 inhibition may lead to the degradation of proteins involved in the so-called six main characteristics of cancer: i) the ability to produce growth factors, ii) resistance to anticancer agents, iii) avoidance of apoptosis, iv) unlimited replicative potential, v) uninterrupted angiogenesis and vi) invasiveness and metastasis (8,12,13). The Hsp90 monomer is composed of four domains: a highly conserved N-and C-terminal domain, a middle domain and a charged linker region that connects to both N-terminal as well as middle domain (14).…”
Section: Hsp90 Inhibitor As a Sensitizer Of Cancer Cells To Differentmentioning
confidence: 99%
“…[8,9] In NSCLC, Hsp90 stabilizes oncogenic proteins such as EGFR, MET, HER2 and AKT. [9,10] We and some other studies have shown that geldanamycin (GM) and its analogues, the benzoquinone ansamycin class were somewhat disappointing [15][16][17][18][19] and new potent Hsp90 inhibitors have therefore been pharmacologically designed and synthesized to offer improved efficacy and acceptable toxicity. NVP-AUY922 (AUY922) is one of these newly designed small-molecule Hsp90 inhibitors based on the 4,5-diarylisoxazole scaffold; it has a much higher affinity for Hsp90 than previous GM analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Although subsequent experiments proved that these natural HSPC1 inhibitors were able to cause the degradation of a wide range of client proteins, the non-specific toxicity of these compounds prevented their clinical use. However, these experiments led to the development of the first clinically applicable HSPC1 inhibitor, 17-AAG (17-allylamino-17-demethoxygeldanamycin, also known as tanespimycin) (Holzbeierlein et al 2010). As a derivative of GA, 17-AAG resulted in the degradation of a variety of oncogenic proteins in a number of tumour cell types, while displaying reduced toxicity.…”
Section: N-terminal Hspc1 Inhibitorsmentioning
confidence: 99%
“…This compound was entered into clinical trials and tested on a broad array of cancers including a large variety of haematological malignancies such as AML, ALL, CML and CLL. Detailed reviews of clinical trial data can be found in Kim et al (2009), Taldone et al (2008) and Holzbeierlein et al (2010). In addition to showing initial promise as a novel therapy in isolation, 17-AAG also demonstrated synergism with a number of chemotherapeutic agents such as Bortezomib (Richardson et al 2010), Trastuzumab (Modi et al 2007) and Paclitaxel (Ramalingam et al 2008).…”
Section: N-terminal Hspc1 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation